Association of Lead Levels and Cerebral Palsy. (23rd March 2017) - Bansal, Neha; Aggarwal, Anju; Faridi, M. M. A.; Sharma, Tusha; Baneerjee, B. D.
Background: Cerebral palsy is a common motor disability in childhood. Raised lead levels affect cognition. Children with cerebral palsy may have raised lead levels, further impairing their residual cognitive motor and behavioral abilities. Environmental exposure and abnormal eating habits may lead to increased lead levels.Aims and Objectives: To measure blood lead levels in children with cerebral palsy and compare them with healthy neurologically normal children. To correlate blood lead levels with environmental factors.Material and Methods: Design : Prospective case-control study. Setting : Tertiary care hospital. Participants : Cases comprised 34 children with cerebral palsy, and controls comprised 34 neurologically normal, age- and sex-matched children. Methods : Clinical and demographic details were recorded as per proforma. Detailed environmental history was recorded to know the source of exposure to lead. These children were investigated and treated as per protocol. Venous blood was collected in ethylenediaminetetraacetic acid vials for analysis of blood lead levels. Lead levels were estimated by Schimadzu Flame AA-6800 (atomic absorption spectrophotometer). Data were analyzed using SPSS version 17. P < .05 was taken as significant.Results: Mean blood lead levels were 9.20 ± 8.31 µg/dL in cerebral palsy cases and 2.89 ± 3.04 µg/dL in their controls ( P < .001). Among children with cerebral palsy, 19 (55.88%) children had blood lead levels ≥5 µg/dL. Lead levels in children with pica were 12.33 ± 10.02 µg/dL in comparison to children with no history of pica, 6.70 ± 4.60 µg/dL ( P = .029). No correlation was found between hemoglobin and blood lead levels in cases and controls.Conclusion: In our study, blood lead levels are raised in children with cerebral palsy. However, further studies are required to show effects of raised levels in these children.